2019
DOI: 10.1002/advs.201802219
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell‐Released Extracellular Vesicles Potentiate the Efficacy of the HBsAg Vaccine by Enhancing B Cell Responses

Abstract: T cells secrete bioactive extracellular vesicles (EVs), but the potential biological effects of CD4+ T cell EVs are not clear. The main purpose of this study is to investigate the effects of CD4+ T cell–derived EVs on B cell responses and examine their role in antigen‐mediated humoral immune responses. In this study, CD4+ T cell EVs are purified from activated CD4+ T cells in vitro. After immunization with the Hepatitis B surface antigen (HBsAg) vaccine, CD4+ T cell EVs‐treated mice show stronger humoral immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 54 publications
(153 reference statements)
1
31
0
Order By: Relevance
“…These results provide us with a new perspective on engineering exosomes to activate the host immune response or directly induce HBV repression. In addition, exosomes released from active CD4+ T cells can promote B cell activation and further enhance the efficiency of the HBsAg vaccine (Lu et al 2019). In a separate study, researchers found that exosomes combined with hepatitis B recombinant antigen induced a humoral immune response similar to the response to HBsAg solution in mice (Jesus et al 2018).…”
Section: Exosomes As Novel Therapies For Hbv Infectionmentioning
confidence: 99%
“…These results provide us with a new perspective on engineering exosomes to activate the host immune response or directly induce HBV repression. In addition, exosomes released from active CD4+ T cells can promote B cell activation and further enhance the efficiency of the HBsAg vaccine (Lu et al 2019). In a separate study, researchers found that exosomes combined with hepatitis B recombinant antigen induced a humoral immune response similar to the response to HBsAg solution in mice (Jesus et al 2018).…”
Section: Exosomes As Novel Therapies For Hbv Infectionmentioning
confidence: 99%
“…On the other hand, exosomes derived from the more antigen-specific subtype CD8 + T cell show antiviral activity associated with membrane proteins secreted via exosomes [142]. Moreover, CD4 + -associated exosomes have been reported to significantly boost B cell activation, proliferation and, thus, antibody production [143,144] and to act as immunoregulators [145]. Exosomes secreted by CD4 + CD25 + Foxp3 Treg cells, a subset of CD4 + T cells, specializing in immune tolerance establishment and maintenance, which use a diverse set of mechanisms to enforce peripheral tolerance, are thought to be deeply involved in immune regulation [146].…”
Section: Exosomes Derived From Immune System-related Cells That Play mentioning
confidence: 99%
“…Increasing evidence has suggested that EVs also participated in T-B cognate interactions. T cell-EVs or their delivered miRNAs/lipids regulated B cell survival, proliferation, and antibody production 4 , 53 , 58 , suggesting that T cell-EVs could be engineered to treat B cell overactivation-related diseases.…”
Section: Characteristics and Functions Of Evs From Cells Associated Wmentioning
confidence: 99%